Modelling health care customer satisfaction: evidence from Serbia - Rajić, Tamara; Rakić, Ana; Milošević, Isidora (Serbian Journal of Management, 2021)
Customer loyalty, with satisfaction of customers as its main precondition, has long been regarded as an overarching goal of service businesses. With the proliferation of health care providers, which brought about rising competitive pressures on the market, the issue of how to satisfy and keep patients has been attracting increasing attention of researchers and health care management. Therefore, this study aims to examine the antecedents of patient satisfaction and its direct and mediated impact on patients’ behavioural intentions in thus far under-studied context of emerging economy’s health care system. The study has been conducted in a primary health care setting, on a convenience sample of 300 patients, by means of structured questionnaire. The application of structural equation modelling (SEM) revealed direct impact of health care service quality on patient satisfaction and its mediated impact on satisfaction, via perceived value of health care services. In addition to direct influence of satisfaction on patients’ behavioural intentions, its total effect on positive intentions of patients is increased by the impact of patient commitment to a health care provider, which, as evidenced by this study’s findings, increases with patient’s rising trust into a health care provider. Implications for theory and practice are discussed and further research directions are provided.